Vitamin D status and its predictors among pre‐school children in Adelaide. (12th November 2014) - Zhou, Shao J; Skeaff, Murray; Makrides, Maria; Gibson, Robert
<x xml:space="preserve">Abstract</x> Aim To assess vitamin D status and its predictors in a representative population sample of pre‐school children in Adelaide (latitude of 35°S). Methods Cross‐sectional survey of children aged between 1 and 5 years from areas of low, medium and high socio‐economic status as identified from the 2001 Census data, Australian Bureau of Statistics. Children were recruited between September 2005 and July 2007 using a door knocking protocol based on a stratified sampling method to obtain a representative sample of this age group. Serum 25‐hydroxyvitamin D (25(OH)D) was determined using a radio‐immunoassay kit. Vitamin D deficiency was defined as serum 25(OH)D) <30 nmol/L and insufficiency defined as serum 25(OH)D ≥30 and <50 nmol/L according to the Institute of Medicine. Results Fifty‐two per cent of eligible children took part in the study. Mean (standard deviation) serum 25(OH)D was 73 (26) nmol/L (n = 221). The prevalence of vitamin D deficiency and insufficiency was 4% and 16%, respectively, with the prevalence being higher in winter (8% and 22%, respectively). Season of the year of blood collection and mother being born in Australia were significant predictors of serum 25(OH)D concentration, but age, sex, socio‐economic status, BMI category or dietary supplement use were not related to vitamin D status. Conclusions Vitamin D status of this representative sample of pre‐school children in Australia is adequate, and the prevalence of vitamin D deficiency is low based on the Institute of Medicine criteria.